New Forms of Communication with the Client on the Tourist Market - Marciszewska, Barbara; Rapacz, Andrzej (Studia Oeconomica Posnaniensia, 2017)
The purpose of the article is to identify the communication forms with a client used by travel agencies and hotels functioning on the Polish tourist market. The study provides the subject literature review regarding communication forms with a customer on the tourist market. The presentation of direct research results is focused on the above-mentioned communication forms, most popular and most frequently used by travel agencies and hotels functioning on the Polish market and remains an integral component of the study. The conducted review and the research results allowed the identification of similarities and differences occurring in the area of communication forms with a customer on Western European and Polish tourist markets. They also indicated these communication forms which should be used more extensively by both travel agencies and hotels operating on the Polish tourist market. The conducted research results enrich the existing knowledge about the discussed subject matter.